Removability of 316L stainless steel cone and block support structures fabricated by Selective Laser Melting (SLM) - Qiqiang Cao; Yuchao Bai; Jiong Zhang; Zhuoqi Shi; Jerry Ying Hsi Fuh; Hao Wang (Materials & Design, 2020)
Support structures are needed due to the complexities of induced structural, thermal and process factors in Selective Laser Melting (SLM). To date, little systematic study is found to unveil the support removability by a post-machining process. This paper presents an experimental study of removing 316L stainless steel cone and block supports by milling. The effect of different supports is identified by the variation in the microhardness distribution and microstructure of the workpieces. The milling performance of cone and block supports at different cutting depths is studied on the surface finish, surface roughness, milling force, and tool wear and chip formation. The cone supports are subjected to severe collapse, whilst the block supports are mainly removed by localized shearing. The milling force and specific cutting energy of cutting block supports are lower than that of cone supports, and so is the tool wear. A finite element method (FEM) model is developed to explain the removal mechanisms. The results of this study provide an essential reference and unique insight into removal of metal support structures. Moreover, the removability of supports, which is derived from the post-processing stage, should be considered as a new factor in the support design for additive manufacturing.